2005
DOI: 10.1002/ange.200462522
|View full text |Cite
|
Sign up to set email alerts
|

Eine effiziente und allgemein anwendbare Fe‐katalysierte Arylierung von Benzylalkoholen und Benzylcarboxylaten

Abstract: Substituierte Arene und Heteroarene können einfach in Gegenwart katalytischer Mengen von billigen und relativ ungiftigen Eisensalzen wie FeCl3 in hohen Ausbeuten und mit hohen Selektivitäten benzyliert werden. Mit Benzylalkoholen werden Diarylmethane praktisch nebenproduktfrei erhalten (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
36
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 68 publications
0
36
0
2
Order By: Relevance
“…Thus any alternative and potentially milder method not dependent on Brønstedt acids must use water-tolerant Lewis acids. Since in the first step benzyl alcohols 3 are produced, the second step in which the latter reacts with a second molecule of the electron-rich arene is closely related to an iron-catalyzed reaction reported by Beller et al [3] this year. Other activated alcohols recently shown to undergo similar reactions are propargylic alcohols, here Uemura et al [4] investigated ruthenium catalysts and Toste et al [5] rhenium catalysts.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Thus any alternative and potentially milder method not dependent on Brønstedt acids must use water-tolerant Lewis acids. Since in the first step benzyl alcohols 3 are produced, the second step in which the latter reacts with a second molecule of the electron-rich arene is closely related to an iron-catalyzed reaction reported by Beller et al [3] this year. Other activated alcohols recently shown to undergo similar reactions are propargylic alcohols, here Uemura et al [4] investigated ruthenium catalysts and Toste et al [5] rhenium catalysts.…”
mentioning
confidence: 87%
“…Another Lewis acid, known to be water-tolerant, is Yb(OTf) 3 . With the same amount of this catalyst after 2 days only 5% conversion to 7 were observed.…”
mentioning
confidence: 99%
“…Remarkable are the Ru-, [3] Re-, [4] and Au-catalyzed [5] propargylation of nucleophiles with propargylic alcohols, the Tsuji-Trost reaction of allylic alcohols with active methylene compounds, [6] the reaction of secondary benzylic alcohols with different nucleophiles catalyzed by La, Sc, or Hf salts, [7] and the Fe-, or Au-catalyzed arylation of benzylic alcohols. [8] In addition, InCl 3 has emerged as a powerful catalyst to perform direct nucleophilic substitution of allylic and benzylic alcohols. [9] Although the catalytic activation of alcohols is thought to be difficult due to the poor leaving ability of the OH group, we have recently found that simple Brønsted acids like p-toluenesulfonic acid monohydrate (PTS) catalyze the direct nucleophilic substitution of propargylic alcohols.…”
mentioning
confidence: 99%
“…[28][29][30] The application of inexpensive, non-toxic, commercially available, and environmentally benign iron complexes as catalysts in chemical syntheses has attracted much attention. [31,32] Recently, iron has been utilized extensively as a catalyst to promote the "traditional" cross-coupling between R 1 X and R 2 M. [33][34][35][36][37][38][39][40][41] Iron catalysts are also involved in many important transformations, such as Friedel-Crafts benzylation, [42,43] carbonylation, [44] oxidation [45,46] and other processes. [47][48][49][50][51][52][53][54] Of great interest are the recently developed oxidative coupling reactions of Ar 1 M with Ar 2 H to generate Ar products by employing Fe complexes as the catalysts.…”
mentioning
confidence: 99%